Neck circumference can differentiate obese from nonobese individuals - Lucas,Raquel Eduardo (2016)
BACKGROUND: Obesity is an important problem of public health with increasing prevalence in the population. The diagnosis is made based on body mass index (BMI) levels; the objective of this study was to determine whether the measurement of the neck circumference may be an option to differentiate non-obese from obese individuals. METHOD: Neck circumference was measured using a graduated tape over the thyroid cartilage, in 50 non-obese individuals (66% women) and 97 obese individuals (65% women), diagnosed by BMI. RESULTS: Neck circumference was higher for obese than for non-obese individuals and higher in men than in women. The values of neck circumferences greater than 42 cm for men and 36 cm for women were associated with obesity, with high sensitivity (98%) and specificity (96%). There is a positive association between neck circumference with weight and BMI in women. Age has a negative correlation with BMI in obese individuals. Obese women have less height than non-obese. CONCLUSION: Neck circumference can differentiate obese from non-obese individuals, with high sensitivity and specificity. It is higher in obese than in non-obese individuals, higher in men than in women, and is associated with the grade of obesity.